Atuação da Comissão Própria de Avaliação (CPA) no Instituto Federal de Educação, Ciência e Tecnologia do Ceará - Saboya, Mariângela do Amaral (2015)
The evaluation of higher education in Brazil stands out nowadays, indicating changes in the relations between Higher Education Institutions (IES) and society, becoming an issue that interests the Government and the several social segments. The expansion of higher education in Brazil has increased concern about the quality of education, thus highlighting the institutional evaluation as an important tool to monitor the education offer, and to pursue the quality advocated by Law No. 9394/96, which established the Guidelines and Bases of National Education (LDB). With the approval of Law No. 10.861/2004, which created the National System of Higher Education Evaluation – SINAES, evaluation has gained new contours by considering the institutional aspect, programs, and students’ performance. To evaluate the institutional aspect, SINAES anticipates that IES should scrutinize the profile and ambience of its performance through a self-evaluation conducted by the Own Evaluation Committee (CPA). This scenario motivates this research, which intends to analyze how the CPA actions become effective at the Federal Institute of Education, Science and Technology of Ceará (IFCE) in the light of SINAES, and what evidence points to the construction of the evaluation culture, and the consequent quality improvement of IFCE under-graduation programs. As a methodological approach, supported by the specific legislation and the theoretical referential related to the subject, the institutional evaluation has been carried out in IES, in their political context, until the establishment of SINAES. Through a predominantly exploratory and descriptive research, with a documentary character, and qualitative and quantitative approach having the case study as a technical procedure, one evidences the history, composition, and how the CPA works at IFCE. Based on the questionnaires applied, the vision of managers and representatives from the academic community about the CPA performance are presented, in addition to the reflections on the weaknesses and strengths of those committees, under the view of their members. The analyses have shown that the CPA has relative visibility among managers, professors, and administrative staff, being less recognized among students. Coping with the weaknesses pointed out by the CPA through the strategic planning actions of IFCE is also identified, besides the main difficulties listed by the CPA members, for the full performance of the committees. Finally, some efforts towards the dissemination of self-evaluation in the institution are evidenced; however there are still many difficulties to be overcome in order to consolidate the evaluation culture.